Pengaruh Project Based Learning Berbantuan Lapbook terhadap Keaktifan Belajar Siswa - Rina Wulandari; Ali Mustadi; Yuli Rahayuningsih (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: The research aims to describe the influence of project-based learning lapbook assisted toward students’ learning activeness on thematic learning at grade five of elementary school. The research is a pre-experimental reseach with one group pretest-postest design method. The population of this research was the grade five students’ elementary school which contained 34 students of Dalangan 1 State Elementary School and Sumberagung State Elementary School. Hypothesis test on project-based learning assisted lapbook and on thematic learning activeness are using t paired test. The research result shows that there are significant influences in application project-based learning model assisted lapbook toward students’ learning activeness in grade V of Elementary School, it is proved with significancy value of 0,000 which is smaller than α = 0,05. t count value is 29,192 > t table 2,0345.  Gain acquisition for students’ learning activeness is 35,5% included with medium category.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pengaruh model project-based learning berbantuan lapbook terhadap keaktifan belajar siswa pada pembelajaran tematik di kelas V SD. Penelitian ini menggunakan jenis penelitian eksperimen jenis pre-experimental dengan metode one group pretest-posttest design. Populasi penelitian ini adalah 34 siswa Sekolah Dasar Negeri Dalangan 1 dan Sekolah Dasar Negeri Sumberagung. Uji hipotesis project-based learning berbantuan lapbook dan keaktifan belajar tematik menggunakan uji t paired. Hasil penelitian menunjukkan adanya pengaruh yang signifikan antara model project-based learning berbantuan lapbook terhadap keaktifan belajar siswa kelas V SD dibuktikan dengan nilai signifikansi 0,000 lebih kecil dari α = 0,05. Nilai t hitung adalah 29.192 > t tabel 2.0345. Perolehan gain untuk variabel keaktifan belajar adalah 35,5% termasuk dalam kategori sedang.